The Role of Zakat In Islamic Banking Institutions In Developing The Economyof The Poorand Needy In Malaysia - Azman Ab Rahman (Tazkia Islamic Finance and Business Review, 2012)
Objective: Based on the report of the Malaysian Zakat Management, business Zakat records among the highest collection from the total Zakat collection. Islamic banking insitutions in Malaysia serves as the main contributor to business Zakat . In Malaysia, there are 17 banks doing trade and investment based on Syariah. Therefore, this article will examine the role of business Zakat in Malaysian Islamic banking institutions in developing the economy of the poor.Methods: This study uses the library study method. Among the reading materials that have been referred include those materials related to the poor, the policy approach formed from selected banks namely Bank A and Bank B, the statistical report of the Islamic banking institutions Zakat , websites on the background of the bank sample and so on.Results: As a general guideline in building a framework, through Zakat distribution management in Islamic banking institutions method which is in terms of the policy and regulations. Beside that, this research also focuses on the Islamic banking institutions concern in helping the poor and needy to enhance their lives and also the forms of assistance given to them.Conclusion: It is hoped that this study will be able to become a platform in the brainstorming of several ideas as to ensure that the Zakat management in Malaysian Islamic banking institutions to become better-arranged and effective other than making sure that the Zakat money given to those who deserve them can really achieve the goals that have been determined in Islam.Keywords : Business Zakat, Islamic Banking Institutions, Economy, The Poor